PERFORMA PROPORSI ZERO-INFLATION PADA REGRESI ZERO-INFLATED NEGATIVE BINOMIAL (STUDI KASUS: DATA TETANUS NEONATORUM DI JAWA TIMUR) - AMALIANA, LUTHFATUL; SA’ADAH, UMU; WARDHANI, NI WAYAN SURYA (E-Jurnal Matematika; Vol 7 No 1 (2018)DO - 10.24843/MTK.2018.v07.i01.p183, 2018)
Tetanus Neonatorum (TN) is an infectious disease that could be prevented by immunization . East Java Province is the highest numbers of TN case in Indonesia . TN data in East Java contain overdispersion and big proportion of zero-inflation (71,05%). The data containing overdispersion and zero-inflation are more appropriately analyzed by using Zero-Inflated Negative Binomial (ZINB) regress ion. The aim of this study are: (1) to know the perform of proportion of zero-inflation for ZINB model and (2) to obtain the optimal proportion of zero-inflation for TN data. The result of this study indicates that the optimal proportion of ZINB model is 64,52% .